On the (futile) task of rating languages - Longa, Víctor M.; López Rivera, Juan J. (Boletín de Filología, 2023)
Languages have undergone a wide variety of evaluations, which have triggered many value-judgements about their worth, i.e. about the better or worse nature of some languages as opposed to others. Currently, this situation still persists, in such a way that the thesis of linguistic egalitarianism is being challenged by several proposals. This paper critically discusses the task of evaluating languages, and it argues that any scientific attempt to rate languages from a linguistic approach should fulfill the basic condition of bringing objective criteria to the fore. However, the paper contends that this condition is not met, and it analyzes four different problems language evaluation is endowed with. The problems convert the proposals of rating languages according to their different worth into arbitrary and decontextualized. We conclude that to construct language rankings (through very different parameters) based on the different worth of languages adds nothing to the scientific knowledge of languages, and, in most cases, it expresses or promotes linguistic prejudice.